Pengetahuan Kader Posyandu dalam Pelaksanaan Deteksi Dini Stunting - Atik Wulandari; Rostika Flora; Nur Alam Fajar (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
One of the health problems related to growth and development in children under five that can have a negative impact in the short and long term is stunting. Stunting is a chronic nutritional problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. This study aims to analyze efforts to increase knowledge of posyandu cadres in carrying out early stunting detection. This research is a literature review of research results in several regions in Indonesia related to early detection of stunting and child development, sources of journal searches through Google Scholar in the period 2018 to 2022 with key words knowledge of posyandu cadres & early detection of stunting and selected research results include 9 different journals. Based on the results of the literature review, it was concluded that there was an increase in knowledge of posyandu cadres before and after simulations were carried out such as education, counseling, training on early stunting detection. Suggestions in this study are that the Puskesmas, the Health Office and related parties can continue to provide information, socialization or training that can increase the knowledge of posyandu cadres related to early stunting detection.